Quick Homework Help

# 5y-3x = -20 3x-3y = 1 ⚑ Flag

by Kaitlyn046 at October 12, 2010

Rearrange this : 5y-3x = -20                        -3y +3x = 1 Add these two equations.  This eliminates the x term 2y = -19 y = -19/2 Substitute this into one of the original equations and solve for x x = -55/6

kroo_jteague October 12, 2010

5y - 3x = -203x - 3y = 1one can solve this problem two similar ways:#1 method is to arrange the equations so that one can eliminate one of the variable; thereby, isolating and solving for one of the variables. This problems lends itself nicely to this method:-3x + 5y = -203x - 3y = 1combine the like terms:2y = -19isolate y with by dividing by 22y/2 = - 19/2perform division operation:y = - 19/2now substitute the value of the y variable into the equations:3 x - 3 (-19/2) = 1distribute -3:3 x + 57/2 = 1eliminate 57/2 from the equation's left side:3x + 57/2 - 57/2 = 1 - 57/2simplify: 3x = 1 - 57/23x = 2/2 - 57/23x = -55/2isolate x with division operation or multiplying by inverse:3x(1/3) = -55/2(1/3)x = -55/6answer set is (-55/6, -19/2)

Steven401 October 22, 2010

The second method is to express one of the variables relationally to the other variable.5y - 3x = -203x - 3y = 1therefore, 3x = 3y + 1isolate x with division operation:3x/3 = (3y + 1)/3perform division operation:x = y + 1/3substitute value for x into either equation:5y -3(y+1/3) = -20distribute -3:5y - 3y - 1 = -20combine like terms:2y = -19solve for y:y = -19/2plug value of y into equation and solve for x

Steven401 October 22, 2010